Strategies for proteomics with incompletely characterized genomes: the proteome of Bos taurus serum. - Wait, R; Miller, I; Eberini, I; Cairoli, F; Veronesi, C; Battocchio, M; Gemeiner, M; Gianazza, E (2002)
A reference map for Bos taurus serum was obtained using proteomic tools: 21 proteins, plus several serum albumin fragments, have been identified in 47 spots. One of the major acute-phase reactants, haptoglobin, was also detected in a pathological serum. A number of technical problems had to be solved. (i) Spot resolution in two-dimensional electrophoresis (2-DE) is not easily optimized, as several proteins have similar molecular mass; different polyacrylamide concentration gradients were used for the analysis of various size ranges. (ii) Identification of proteins through mass spectrometry (MS) procedures is also difficult as the genome of Bos taurus is incompletely characterized. The program FASTS proved particularly useful, since it allows simultaneous searching of several unordered sequence fragments, which may be individually too short to provide a statistically valid match using BLAST.